2016
DOI: 10.7863/ultra.15.02026
|View full text |Cite
|
Sign up to set email alerts
|

Portable A‐Mode Ultrasound for Body Composition Assessment in Adolescents

Abstract: This study has shown that US applied in a specific regression for BF% prediction in adolescents

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 17 publications
2
7
0
Order By: Relevance
“…The addition of those two sites, especially the abdominal fold in the current obese population, may have contributed to the discrepant findings. Additionally, a few recent papers have reported similar validity to the present study when using less sophisticated amplitude (A)-mode ultrasound units (Ripka , et al 2016; Smith-Ryan , et al 2014). These investigations have demonstrated US to underestimate %Fat in young normal weight adults (Ripka , et al 2016), and overestimate in overweight and obese adults (Schoenfeld , et al 2016; Smith-Ryan , et al 2014).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The addition of those two sites, especially the abdominal fold in the current obese population, may have contributed to the discrepant findings. Additionally, a few recent papers have reported similar validity to the present study when using less sophisticated amplitude (A)-mode ultrasound units (Ripka , et al 2016; Smith-Ryan , et al 2014). These investigations have demonstrated US to underestimate %Fat in young normal weight adults (Ripka , et al 2016), and overestimate in overweight and obese adults (Schoenfeld , et al 2016; Smith-Ryan , et al 2014).…”
Section: Discussionsupporting
confidence: 86%
“…Additionally, a few recent papers have reported similar validity to the present study when using less-sophisticated amplitude (A)-mode ultrasound units (Smith-Ryan et al, 2014;Ripka et al, 2016). These investigations have demonstrated US to underestimate %Fat in young normal weight adults (Ripka et al, 2016), and overestimate in overweight and obese adults (Smith-Ryan et al, 2014;Schoenfeld et al, 2016). Similarly, the B-mode US in the current study provided an overestimation of %Fat in an OW/OB sample.…”
Section: Discussionsupporting
confidence: 85%
“…Utter and Hagger [36] showed that the ultrasound estimates of fat-free mass was significantly correlated with the estimate from hydrostatic weighing (r=0.97). Ripka et al [37] showed that ultrasound applied in a specific regression for BF% prediction in 71 adolescents has a strong correlation (r=0.848) with DXA.…”
Section: Wagner Et Al [32] Evaluated the Validity And Reliability Ofmentioning
confidence: 99%
“…Therefore, with a stronger echo return there is a higher amplitude spike and, thus, the fat tissue boundary can be identified (29). It is important to note that the BodyMetrix software automatically identifies the amplitude spike, and this approach showed questionable validity (3,7,11,12,19,23,26,27), but excellent reliability (12,23,27) in estimating body fat percentage. Although its excellent reliability for body fat percentage evaluation could support GT BM as a reliable tool in measuring fat thickness, information regarding its precision for different body sites is not available.…”
Section: Introductionmentioning
confidence: 99%